A novel approach for segmentation and quantitative analysis of breast calcification in mammograms - Tong, Yunfei; Jiang, Jianrong; Chen, Fang; Guo, Guanghua; Zhang, Chaoren; Deng, Tiana (Frontiers in Oncology, 2024)
Background: Breast cancer is a major threat to women's health globally. Early detection of breast cancer is crucial for saving lives. One important early sign is the appearance of breast calcification in mammograms. Accurate segmentation and analysis of calcification can improve diagnosis and prognosis. However, small size and diffuse distribution make calcification prone to oversight.Purpose: This study aims to develop an efficient approach for segmenting and quantitatively analyzing breast calcification from mammograms. The goal is assisting radiologists in discerning benign versus malignant lesions to guide patient management.: This study develops a framework for breast calcification segmentation and analysis using mammograms. A Pro UNeXt algorithm is proposed to accurately segment calcification lesions by enhancing the UNeXt architecture with a microcalcification detection block, fused-MBConv modules, multiple loss functions training, and data augmentation. Quantitative features are then extracted from the segmented calcification, including morphology, size, density, and spatial distribution. These features are used to train machine learning classifiers to categorize lesions as malignant or benign. Results: The proposed Pro UNeXt algorithm achieved superior segmentation performance versus UNet and UNeXt models on both public and private mammogram datasets. It attained a Dice score of 0.823 for microcalcification detection on the public dataset, demonstrating its accuracy for small lesions. For quantitative analysis, the extracted calcification features enabled high malignant/benign classification, with AdaBoost reaching an AUC of 0.97 on the private dataset. The consistent results across datasets validate the representative and discerning capabilities of the proposed features. Conclusion: This study develops an efficient framework integrating customized segmentation and quantitative analysis of breast calcification. Pro UNeXt offers precise localization of 1 Yunfei Tong et al. calcification lesions. Subsequent feature quantification and machine learning classification provides comprehensive malignant/benign assessment. This end-to-end solution can assist clinicians in early diagnosis, treatment planning and follow-up for breast cancer patients.